Haematogenous muscular metastasis of non-small cell lung cancer in F-18 fluorodeoxyglucose positron emission tomography/computed tomography - Savas, Karyagar; Pinar, Koc Zehra; Sevda, Karyagar Saglampinar; Ugur, Kesici; Evrim, Savli; Halit, Cinarka; Ansal, Balci Tansel (Termedia Publishing House Ltd, 2015)
Aim of the study: F-18 FDG PET/CT is the most effective method for demonstrating extrapulmonary metastases of lung cancer. The aim of this study is to investigate the level of muscular metastasis of non-small-cell lung carcinoma (NSCLC) in F-18 FDG PET/CT and to demonstrate the characteristics of this special group of patients. Material and methods: A total of 1150 patients with the diagnosis of NSCLC, who were referred for F-18 FDG PET/CT, were included into the study. Among these patients, the findings of 13 who were shown to have muscle metastases were studied. Results: In the retrospective analysis of the patients, 13 patients (12 male, 1 female; mean: 59 +/- 7 years old) were found to have haematogenous (excluding local invasion) muscular metastases of NSCLC using F-18 FDG PET/CT. Two of the 13 patients had only muscular metastases (one patient isolated, one patient two foci). The other 11 patients had additional distant metastases in six metastatic sites (bone in 7 patients, distant lymph node in 6, adrenal gland in 5, contralateral lung in 3, liver in 1, and brain metastasis in 1 patient). Five patients died during the mean 11 +/- 8 months follow up. Conclusions: Muscular metastasis is not a rare condition, especially in F-18 FDG PET/CT examinations, and is frequently associated with additional distant metastases.
Keywords: lung cancer; F-18 FDG PET/CT; muscular metastasis